2011
DOI: 10.2319/032011-197.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two different techniques for early correction of Class III malocclusion

Abstract: Objective: To compare the effectiveness of Reverse Twin-Block therapy (RTB) and protraction face mask treatment (PFM) with respect to an untreated control in the correction of developing Class III malocclusion. Materials and Methods: A retrospective comparative study of subjects treated cases with either PFM (n 5 9) or RTB (n 5 13) and untreated matched controls (n 5 10) was performed. Both the PFM and control group samples were derived from a previously conducted clinical trial, and the RTB group was formed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
5
43
2
9
Order By: Relevance
“…In several FM studies, a backward rotation of the mandible and an increase in lower facial height were reported. 11,27 However, some studies 5,28 reported that the posterior/anterior face-height ratio remained unchanged; in accordance with this finding, a nonsignificant change was observed in the SN/GoGn angle. The significant decrease in overbite in the treatment groups might be due to maxillary incisor protrusion and changes in lower facial height.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In several FM studies, a backward rotation of the mandible and an increase in lower facial height were reported. 11,27 However, some studies 5,28 reported that the posterior/anterior face-height ratio remained unchanged; in accordance with this finding, a nonsignificant change was observed in the SN/GoGn angle. The significant decrease in overbite in the treatment groups might be due to maxillary incisor protrusion and changes in lower facial height.…”
Section: Discussionsupporting
confidence: 72%
“…Tortop et al 30 concluded that changes in upper incisors resulting from treatment with modified tandem traction bow appliance could be responsible for the overjet difference compared with FM treatment. Seehra et al 27 reported that both FM and reverse twin block therapies resulted in similar overjet changes. In molar relation, the significant increase was greater in the DPA-FM group than in the FM group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If left untreated, Class III malocclusion in the growing children will become worse with age, presented by the growth of the mandible exceeding the growth of the maxilla [1,2,5]. This unfavourable growth can also occur late in adolescence or in early adulthood, especially in relation to mandibular prognathism.…”
Section: Introductionmentioning
confidence: 99%
“…This unfavourable growth can also occur late in adolescence or in early adulthood, especially in relation to mandibular prognathism. Hence, although in Class III cases that are successfully treated, there is still a risk thatthe Class III growth pattern may re-establish itself [1,5,6].…”
Section: Introductionmentioning
confidence: 99%